Historical and Cultural Pathways Toward Gender Equality and Social Justice - Putri, Wahdania; Noviani, Teresia; Saputra, Febrian (Journal Social Humanity Perspective, 2025)
This paper taps on the historical and cultural avenues to have created gender equality and social justice by contextualizing the research topic to the bigger area of study in management. Using qualitative approach, the research will provide insight into how tradition legacies, culture, and practices within an institution affect the way contemporary organizations operate. Instead of assuming equality as a regulatory compliance issue, the results reiterate the fact that the way in which any management is conducted is shaped within historical memories and cultural settings that either perpetuate the structural inequality or break it. The work shows that historical hierarchies and cultural conventions have not completely disappeared in the decision-making process, leadership methods and the organizational culture of managers. Solutions to these must involve going beyond symbolic practices to systemic changes that incorporate equity into fundamental approaches to human resource management, governance and accountability. Critically, analysis has also determined that addition of sensitivity to historical and cultural awareness into organizational practices does not only promote social justice but also fosters legitimacy, trust and ability to adapt in the long-term in diversifying and globalizing societies. This study is relevant to management research as it has shown that a properly grounded appreciation of culturally and historically informed approaches proves effective in the design of fair organizations. It also offers practical knowledge to leaders who are willing to cultivate justice-oriented management systems that can unify ethical demands with strategy-making competences.